Expert Advisor Construction Using Fixed Fractional Money Management and Williams Percent-R Indicator In DAX-30 (DE30) Trading: Analysis on Zero Spread Account - Vetric Styven Silaban; Haikal Rahman; Dedy Husrizal Syah (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the effectiveness of an automated strategy for trading the DAX-30 index through the construction of an Expert Advisor integrating the Williams Percent Range indicator and the Fixed Fractional Money Management method. The strategy was tested on a Zero Spread account, which offers zero spreads with a fixed commission per lot, to assess the impact of the fee structure on profitability. A prototype Expert Advisor was developed and tested using historical and real-time data on the MetaTrader 5 platform. Backtesting results showed that the combination of the Williams Percent Range indicator and the risk management method produced consistent performance, with an adequate profit ratio and controlled drawdown. Implementing the strategy on a Zero Spread account improved execution precision and risk calculation accuracy, significantly impacting equity curve consistency. Real-time testing demonstrated that eliminating variable spreads improved the validity of technical signals and the effectiveness of risk management. This study concluded that the combination of a technical approach and automated risk management can optimize trading strategy performance in volatile market conditions.